2018
DOI: 10.1002/jca.21669
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vascular access devices upon efficiency of therapeutic plasma exchange

Abstract: Background An efficient vascular access is mandatory for the proper conduction of therapeutic plasma exchanges (TPE). Peripheral and central venous catheters may be used, with respective advantages and limitations. In this study, vascular access devices (IV catheter, dialysis cannula, central venous catheter) and anatomic vein characteristics were evaluated. Method From January to June 2016, 162 TPE in 29 patients were reviewed. Only TPE using centrifugation method (Spectra Optia apheresis system) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Antecubital fossa and larger arm veins such as cephalic or basilic are recommended for drawing blood from the patient; whereas, we can use smaller veins for return. Ritzenthaler et al evaluated the influence of vascular access devices and anatomic characterization of veins upon TPE efficiency [15]. They used two different PVCs: IV catheter (16 or 18 G) or dialysis cannula (18G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antecubital fossa and larger arm veins such as cephalic or basilic are recommended for drawing blood from the patient; whereas, we can use smaller veins for return. Ritzenthaler et al evaluated the influence of vascular access devices and anatomic characterization of veins upon TPE efficiency [15]. They used two different PVCs: IV catheter (16 or 18 G) or dialysis cannula (18G).…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, PVC was chosen to be the first option in TPE vascular access in inpatient and outpatient settings, as it is more convenient and has lesser risk of complications. Besides, US-guided peripheral access was reported to help prevent CVC insertion in up to 10% of the procedures [15]. [20]…”
Section: Pva Complicationsmentioning
confidence: 99%
“…An international apheresis registry found the highest rates of access problems with peripheral venous access and AVF or AVG use . A single center study observed higher rates of inlet pressure pauses and longer procedure duration with peripheral venous access . Low inlet pressure alarms with peripheral access may be due to vein collapse at the tip of the access needle .…”
Section: Discussionmentioning
confidence: 99%
“…In a nationwide study of TPE, predictors of CVC use were obesity (18% vs. 16%, P = 0.017), concurrent hemodialysis (14% vs. 10%, P < 0.001), female sex (54% vs. 50%, and illness severity ( P < 0.001) 3 . CVC has been preferred over peripheral venous access due to access difficulties, longer procedural times, suboptimal blood flow, inadequate process volume, and decreased efficiency 2,7,40‐42 . Notwithstanding these challenges, peripheral venous access is associated with lower rates of adverse events 2,7,42 .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the ASFA Choosing Wisely campaign recommends peripheral venous access over CVC 3,40 . Peripheral venous access could be optimized by ultrasound‐guided peripheral vein assessment as shown in a French study in which peripheral vein assessment by ultrasound allowed successful peripheral venous access in 64% of the procedures 41 . Ultrasound assessment should be considered as a strategy to increase peripheral access in eligible inpatients undergoing TPE.…”
Section: Discussionmentioning
confidence: 99%